Modelling Of Inhomogeneous Vertical Underwater Optical Wireless Communication Links - Sabril, Muhammad Safiy (2023)
Underwater optical wireless communication (UOWC) is becoming increasingly widespread, moving beyond its former restriction to military and defense applications to now also being used in commercial fields. Despite its growing popularity, designing UOWC systems is challenging due to the complex interaction of light with water. To overcome these challenges, this thesis proposes using inhomogeneous medium in UOWC channel modeling, as opposed to the traditional homogeneous medium model which assumes a single constant value for the ocean’s physical and chemical properties. The thesis presents two inhomogeneous models: Model II, based on the variation in chlorophyll concentration, and Model III, which includes the variation in both chlorophyll concentration and refractive index. These models are compared to Model I, the homogeneous model. To estimate the received power, channel bandwidth, and delay spread, the Monte Carlo (MC) technique was improved to account for medium inhomogeneity.